Kontrol Kecepatan dan Temperatur dengan Teknik Pulse Widht Modulation untuk Aplikasi Hotplate Stirrer Berbasis Arduino - Junaidi Junaidi; Handani Wahyu Hesti; Suciyati Wahyu Sri; Supriyanto Amir (Lambung Mangkurat University Press, 2020)
In this research, design and realization of temperature and speed control instrument using thermocouple and pulse width modulation based on arduino for hotplate stirrer aplication have been carried out. This instrument is laboratory tool used for stiring and heating a chemical liquid with capability up to 1200 rpm and 300 oC, respectively. The main components used in the manufacture of hotplate stirrer are Arduino mega, DC motor, tubular heater, LM393 optocoupler sensor, MAX6675 type-K thermocouple, and sevent segment. The hotplate stirrer has a tolerance of rotational speed measurement of ±5 rpm and a tolerance of temperature measurement of ±5 oC. The accuracy of temperature and rotating speed measurement in this instrument about 0,25 oC and 2 rpm. Based on its capabilities, this instrument can be applied to research on synthesis of material at the micro and nano scale.